AT THE GRASSROOTS: AIDS AND PEOPLE IN SOUTH AFRICA. - Whiteside, Alan (PINS-Psychology in Society, 2025)
Squire, C (2007) HIV in South Africa. London: Routledge. ISBN 978-0-415-37210-7. Pages 229. The HIV/AIDS epidemic in South Africa has been well documented. There have been books that tried to understand why the epidemic is so serious and what has driven the response, in particular the baffling politics of AIDS. These included the classic ethnography by Campbell (2003), Fourie (2006), Nattrass (2007) and Lawson (2008). Biographical accounts included Cameron (2005) and McGregor (2006). The epidemic makes an appearance in South African fiction, from books specifically centred on it (Steyn, 2007); to those where it is in the background (Morojele, 2006); to mentions in detective fiction (Meyer, 1999). There have been moving exhibitions, both photographic and in other media, documenting the scale and effect of HIV/AIDS. Most of these books are written by white South Africans. The voice of the people is generally not heard, although the perceptive book by Nolen (2007) (a white Canadian journalist living in Johannesburg) goes some way to redress this.